CHANGING THE CONSTRUCTION OF THE WORKING CHAMBER IN ORDER TO SEPARATION OF COTTON FIBER FROM CHARGE (American Journal of Interdisciplinary Research and Development, 2024)
According to the results of the literature analysis conducted in the scientific article in order to determine the main factors affecting the increase in density and the loss of the natural quality of the fiber in the process of fiber separation, the most important of them was the presence of unginned seed cotton in the working chamber. . We would like to give an overview of the new working chamber for the control of the technological process of the two-chamber working body, which ensures the preservation of the natural properties of seed cotton and its products, and for saw fiber separators.